Siloxane-containing copolymers and articles
By using the copolymer formed by (meth)acrylate group polymerization, the existing copolymers lose water repellency and insufficient oil repellency to oil after washing and drying, and the copolymers remain highly water repellent and oil repellent after multiple uses.
Patent Information
- Application Number
- CN202411071702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2024-08-06
- Publication Date
- 2025-03-21
AI Technical Summary
The existing copolymers lose their water repellency after washing and drying, and have insufficient oil repellency to oil, making it difficult to maintain performance after multiple uses.
A copolymer formed by polymerization of (meth)acrylate groups, which comprises ethylenically unsaturated comonomers with functional groups and silicon-containing monomers, is prepared by radical polymerization technology, increasing the water and oil repellency of the copolymer.
The copolymer has achieved high water repellency after washing and drying, and has good oil repellency to oil, extending its service life.
Smart Images

Figure CN119663637A_ABST
Abstract
Description
Summary of the invention
[0001] In one embodiment, a copolymer is described, the copolymer comprising:
[0002] a) 50 to 95 wt. % of first polymerized units comprising
[0003] At least one of the following:
[0004] a1)
[0005] or
[0006] a2)
[0007]
[0008] in:
[0009] Each R 1 are independently H or methyl;
[0010] Each R 2 are independently methyl or ethyl;
[0011] Each R 3 are independently methylene, ethylene or propylene;
[0012] Each R 4 are independently methyl, ethyl, propyl or butyl;
[0013] Each n is independently an integer from 2 to 10; and
[0014] b) 5 to 50 wt% of a second polymerized unit represented by the formula:
[0015]
[0016] in:
[0017] Each R 6 are independently methylene, ethylene or propylene; and
[0018] X is independently a functional group selected from epoxy, hydroxyl or isocyanate; and
[0019] c) Optional further comonomers.
[0020] In an advantageous embodiment, R 1 , R 2 , R 3 , R 4 , n and X are selected to provide high oil repellency. 1 , R 2 and R4 In this embodiment, R 3 In some embodiments, n is generally not greater than 10.
[0021] The amount of optional comonomer is typically no greater than 20, 15, 10, 5 or 1 weight percent.
[0022] Also described is an article comprising a substrate and a copolymer disposed on at least a portion of the substrate. DETAILED DESCRIPTION
[0023] The (meth)acrylic copolymer is prepared by copolymerizing at least one ethylenically unsaturated silicon-containing monomer with an ethylenically unsaturated comonomer having a functional group.
[0024] In a typical embodiment, the ethylenically unsaturated group of the monomer is a (meth)acrylate group, ie, acrylate or methacrylate. The polymerization of the (meth)acrylate group forms a copolymer having a (meth)acrylic backbone and containing silicone side groups and functional side groups.
[0025] Silicon-containing (meth)acrylate monomers are commercially available. Examples of commercially available monomers suitable for forming monomer units a1) include 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, available, for example, as Wacker CLA 30 from Wacker Chemie AG. The monomer 3-[tris(trimethylsiloxy)silyl]propyl methacrylate can also be purchased from Silar Laboratories, Sigma-Aldrich, St. Louis, Missouri, and Career Henan Chemical Company, Zhengzhou, China. Examples of commercially available monomers suitable for forming monomer units a2) include, for example, monomethacryloxypropyl terminated polydimethylsiloxane MCR-M17 (1000 g / mol, available from Gelest, Inc., Morrisville, Pennsylvania, USA); monomethacrylate terminated poly(dimethylsiloxane) (available from Sigma-Aldrich as Cat. No. 798274); X-22-2404 medium chain, single-terminated methacrylate modified silicone resin (400 g / mol side chain, available from Shin-Etsu Chemical Co., Ltd., Tokyo, Japan); Co., Tokyo, Japan); X-22-174ASX medium-chain, single-end methacrylate-modified silicone resin (900 g / mol side chain, available from Shin-Etsu Chemical Co., Ltd.); X-22-174BX medium-chain, single-end methacrylate-modified silicone resin (2300 g / mol side chain, available from Shin-Etsu Silicones of America, Akron, Ohio); and KF-2012 medium-chain, single-end methacrylate-modified silicone resin (4600 g / mol side chain, available from Shin-Etsu Chemical Co., Ltd.).
[0026] Some representative monomers are described below:
[0027]
[0028]
[0029] Each n is independently an integer from 2 to 65. In some embodiments, n is independently an integer from 10 to 65. In some embodiments, n is independently an integer from 20 to 65. In some embodiments, n is independently an integer from 30 to 65. In some embodiments, n is independently an integer from 40 to 65. In some embodiments, n is independently an integer from 2 to 50. In some embodiments, n is independently an integer from 5 to 50. In some embodiments, n is independently an integer from 10 to 50. In some embodiments, n is independently an integer from 20 to 50. In some embodiments, n is independently an integer from 15 to 45. In some embodiments, n is independently an integer from 25 to 45. In typical embodiments, monomer units with different n values may be present, but this is not necessary. In some advantageous embodiments, n is not greater than 10.
[0030] In some embodiments, the silicon-containing (meth)acrylate monomer has a functional group equivalent weight (or in other words, the molecular weight per functional group) in the range of 200 g / mol to 1000 g / mol. In some embodiments, the functional group equivalent weight is no greater than 900 g / mol, 800 g / mol, 700 g / mol, 600 g / mol, 500 g / mol, or 400 g / mol.
[0031] In some embodiments, the copolymer comprises monomer unit a1. In some embodiments, the copolymer comprises monomer unit a2. In other embodiments, the copolymer may comprise monomer units a1 and a2. In this embodiment, the molar ratio of a1:a2 is in the range of 1:10 to 10:1.
[0032] The total amount of monomer units a) is typically at least 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95% by weight, based on the total weight of the copolymer. In some embodiments, the amount of monomer units a) is no greater than 95%, 90%, 85%, 80%, or 75% by weight, based on the total weight of the copolymer.
[0033] The copolymer comprises at least one second divalent monomer unit b), the at least one second divalent monomer unit being represented by the formula:
[0034]
[0035] in:
[0036] Each R 6 are independently methylene, ethylene or propylene; and
[0037] X is a functional group selected from epoxy, hydroxyl or isocyanate.
[0038] In an advantageous embodiment, where the copolymer is a water-based dispersion, X is preferably an epoxy group, such as in the case of glycidyl (meth)acrylate. In this embodiment, at least 50%, 60%, 70%, 80%, 90%, or 100% of the X groups are epoxy groups. In this embodiment, less than 50%, 40%, 30%, 20%, or 10% of the X groups are other functional groups, such as hydroxyl and / or isocyanate.
[0039] Comonomers suitable for generating monomer unit b are commercially available and include, for example, glycidyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, isocyanoethyl acrylate, isocyanoethyl methacrylate (IEM), and blocked isocyanates (such as 2-[O-[1′-methylpropylideneamino]carboxyamino)ethyl methacrylate and 2-[(3,5-dimethylpyrazolyl)carboxyamino]ethyl (meth)acrylate). In some embodiments, the blocked isocyanate has a deblocking temperature of at least 80°C, 90°C, 100°C, or 110°C. The deblocking temperature of the blocked isocyanate generally has a deblocking temperature below the drying temperature. In some embodiments, the blocked isocyanate has a deblocking temperature of no greater than 170°C, 160°C, 150°C, 140°C, 130°C, or 120°C. When the copolymer is a water-based dispersion, a blocked isocyanate is preferably used to prevent reactions within the dispersion prior to applying the dispersion to a substrate.
[0040] The total amount of monomer units b) is typically no greater than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5% by weight, based on the total weight of the copolymer. In some embodiments, the amount of monomer units b) is at least 5%, 10%, 15%, 20%, or 25% by weight, based on the total weight of the copolymer.
[0041] Without being bound by theory, it is speculated that the functional group X (eg, epoxy) can crosslink with itself or with other functional groups present in the composition or functional groups present on the substrate.
[0042] Optional monomers
[0043] The copolymer may optionally include other monomers. When present, the amount of other monomers is generally not more than 20%, 15% or 10% by weight based on the total weight of the copolymer. In some embodiments, the amount of other monomers is not more than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2% or 1% by weight based on the total weight of the copolymer.
[0044] In typical embodiments, the optional monomers can be characterized as hydrophobic monomers. However, it is speculated that low concentrations of hydrophilic monomers may also be suitable. For example, the hydroxyl functional comonomers described herein can be considered hydrophilic monomers.
[0045] Examples of hydrophobic monomers include (meth)acrylates and (meth)acrylamides, which contain a linear or branched alkyl group having 1 to 24 carbon atoms. Specific examples include hydrophobic monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, propyl (meth)acrylamide, butyl (meth)acrylamide, tert-butyl (meth)acrylamide, hexyl (meth)acrylate, octyl (meth)acrylamide, and lauryl (meth)acrylamide.
[0046] Method for preparing copolymers
[0047] Copolymers according to the present disclosure can be prepared, for example, by free radical polymerization using known techniques. For example, free radical polymerizable monomers (typically in water and / or an organic solvent) can be mixed with a thermally activated free radical initiator (e.g., a peroxide or an azo compound) and then heated under an inert atmosphere. Alternatively, other techniques can be used, such as, for example, ionizing radiation or ultraviolet radiation in combination with an included free radical photoinitiator (e.g., benzophenone or α-cyclohexyl-α, α-dimethoxyacetophenone).
[0048] Examples of suitable thermal initiators include peroxides (e.g., benzoyl peroxide, dibenzoyl peroxide, dilauroyl peroxide, cyclohexane peroxide, and methyl ethyl ketone peroxide), hydroperoxides (e.g., butyl hydroperoxide and isopropylbenzene hydroperoxide), dicyclohexyl peroxydicarbonate, tert-butyl perbenzoate, and azo compounds (such as 2,2-azo-bis(isobutyronitrile) (AIBN)), and combinations thereof. Examples of commercially available thermal initiators include initiators such as VAZO 64 (2,2′-azobis(isobutyronitrile)), VAZO 52, VAZO 65, and VAZO 68, available under the trade name “VAZO” from The Chemours Company (Wilmington, Delaware), U.S.A., and initiators available under the trade name “CELOGEN” from CelChem LLC, Naples, FL, U.S.A. Peroxides are available from a variety of sources.
[0049] The use amount of free radical polymerization initiator can effectively cause the free radical polymerization of free radical polymerizable monomers. This amount is usually different depending on the following factors: for example, the type of initiator, the molecular weight of the initiator, the expected application of the copolymer composition and polymerization process factors (such as temperature). The free radical initiator can be used in any amount, and this amount can effectively promote the polymerization of the monomer, for example, every hundred weight parts of the total amount of the copolymer is 0.1 weight part to about 5 weight parts, 0.2 weight part to about 2 weight parts or about 0.1 weight part to about 1 weight part.
[0050] If it is desired to control the molecular weight distribution of the copolymer, a free radical polymerization chain transfer agent may be added to the combined monomers prior to polymerization. Examples of available chain transfer agents include, but are not limited to, those selected from the group consisting of carbon tetrabromide, alcohols, mercaptans, and mixtures thereof. Some preferred examples include thioglycerol, isooctyl thioglycolate, tert-dodecyl mercaptan, tert-nonyl mercaptan, n-octyl mercaptan, 1,8-dimercapto-3,6-dioxaoctane (DMDO), isooctyl 3-mercaptopropionate.
[0051] If present, chain transfer agents are typically present in amounts up to about 1 part by weight, typically from about 0.01 to about 0.5 parts by weight, and if used, preferably from about 0.05 to about 0.2 parts by weight, based on 100 parts by weight of the combined monomers present.
[0052] The copolymers described herein can be characterized as random copolymers.
[0053] Copolymers according to the present disclosure may be dispersed and / or dissolved in a liquid carrier to facilitate application to a substrate. Suitable liquid carriers may include water, organic solvents (e.g., ethers, esters, alcohols, ketones, chlorinated hydrocarbons and / or hydrocarbons). In some embodiments (e.g., those involving aerosol dispensers), liquefied and / or compressed gases may be combined with the copolymers.
[0054] In some cases, the copolymer can be synthesized in an organic solvent and then emulsified into an aqueous dispersion. The dispersion will generally comprise water, an effective amount of the composition capable of providing repellency properties to the substrate treated with the composition, and an effective amount of a surfactant capable of stabilizing the dispersion. Conventional cationic surfactants, nonionic surfactants, anionic surfactants, or mixtures thereof are suitable.
[0055] The non-fluorinated water repellent treatment comprising the copolymer as described herein may optionally comprise one or more additional components such as, for example, an antioxidant, an ultraviolet (UV) light stabilizer, or an optical brightener.
[0056] The copolymers according to the present disclosure can provide a degree of oil repellency to a substrate (ie, a solid substrate).
[0057] The substrate may comprise an organic material, an inorganic material, or a combination thereof. In some embodiments, the substrate comprises a porous surface including paper, woven and nonwoven fabrics, natural and synthetic leather or suede; and a hard surface including concrete and natural and synthetic wood and stone.
[0058] The copolymers described herein contain monomers having cure sites (ie, X of the divalent unit b). The term "cure site" refers to a functional group that is capable of participating in a reaction such that it can be bonded to a substrate to be treated to impart durability of certain properties.
[0059] In many embodiments, the non-fluorinated oil repellent treatment agent can be applied to the substrate while being carried in a liquid carrier that evaporates after application (e.g., by spraying, dipping, or long-term soaking). After applying the treatment solution, the substrate can be dried in an oven at any suitable temperature (usually in the range of 100° C. to 200° C.) for up to several minutes.
[0060] According to the test method described in the embodiment, water repellency and oil repellency are evaluated.It is noteworthy that the 3-(methacryloyloxy)propyl tris(trimethylsiloxy)silane (C1 of the embodiment) of solidification has high (85-100) initial water repellency on the fabric including polyester fabric, polyamide fabric and polyester-cotton fabric.Similarly, the X-22-2404 (C2 of the embodiment) of solidification also has high (70-100) initial water repellency on the fabric including PES as polyester fabric, PA as polyamide fabric and PES / Co as polyester-cotton fabric.However, both C1 and C2 do not show water repellency after washing and drying.C1 and C2 also have good (i.e. grade A or B) initial oil repellency to the oil including mineral oil and olive oil.
[0061] The copolymers described herein that also include polymeric units b) having functional groups provide comparable or better initial water repellency. The initial water repellency on fabrics including polyester fabrics, polyamide fabrics and polyester-cotton fabrics is at least 70, 80, 90 or 100. The inclusion of polymeric units b) having functional groups improves water repellency after washing and drying. The water repellency after washing and drying on fabrics including polyester fabrics, polyamide fabrics and polyester-cotton fabrics can be at least 50, 60, 70, 80, 90 or 100. The copolymers described herein that also include polymeric units b) having functional groups also exhibit good (i.e., grade A or B) initial oil repellency.
[0062] Objects and advantages of this disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.
[0063] Example
[0064] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight. Table 1 below describes the materials used in the examples.
[0065]
[0066] Test Method
[0067] Oil repellency
[0068] Initial oil repellency was evaluated using test oil 1 (i.e., mineral oil and olive oil) according to American Association of Textile Chemists and Colorists (AATCC) TM118-2013e2, Test Method for Oil Repellency: Hydrocarbon Resistance. As specified in the test method, oil repellency was graded according to the following criteria.
[0069] A = Acceptable; clear round droplets.
[0070] B = Just pass, partially darkened round drop.
[0071] Fail - Wicking is evident and / or completely wetted
[0072] Water repellency
[0073] Water repellency is measured by AATCC™ 22-2017e, Test Method for Water Repellency: Spray, and is expressed as a "Water Rating" of the fiber substrate tested.
[0074] The wetting rating of the treated fiber substrate is a value indicating the dynamic repellency of the treated substrate to water impinging on the treated substrate (PES is polyester fabric, PA is polyamide fabric, PES / Co is polyester cotton fabric). The wetting rating (SR) is obtained by spraying 250 milliliters (mL) of water on the substrate from a height of 15 centimeters (cm). As specified in the test method, the wetting pattern is visually rated using a 0 to 100 scale, where 0 means complete wetting and 100 means no wetting at all. The wetting rating (IN SR) is measured initially, and then the fiber substrate is washed 10 times.
[0075] washing
[0076] The washing process involves washing 400-900 cm of the treated fiber substrate. 2The sheet was placed in a washing machine (Miele Novotronic T490) along with a ballast sample (1.9 kilograms (kg) of 8 ounces of fabric). A commercial detergent ("Sapton", available from Henkel, Germany, 60 grams (g)) was added. The fiber substrate and ballast load were washed at 40°C using a short wash cycle, followed by a rinse cycle and centrifugation. The samples were not dried between repeated cycles. After 10 wash cycles, the samples were dried in a Miele T-356 tumble dryer set to "extreme dry". The samples were conditioned at room temperature overnight and then tested for water pick-up levels. The results for the water pick-up levels are expressed as SR 10LD TD, respectively.
[0077] Treatment via padding process: Water-based dispersions
[0078] Prior to application to a fiber substrate (e.g., a textile or fabric substrate), a 30% polymer dispersion was diluted with deionized water to obtain a treatment dispersion with a concentration of 33 g / liter of active material to produce 1% solids on the fiber substrate. The treatment was applied to the fiber substrate by immersing the substrate in the treatment dispersion and stirring until the substrate reached saturation. The saturated fiber substrate was then passed through a padder / roller to remove excess dispersion and obtain a certain percentage (%) of moisture absorption (WPU) (100% WPU means that after the process, the substrate absorbs 100% of its own weight of the pre-drying treatment dispersion). After applying the treatment dispersion, the treated substrate was dried and cured at 155°C for 3 minutes unless otherwise stated. The dried samples were conditioned at room temperature overnight before testing.
[0079] General procedure for synthesizing polymer dispersions
[0080] A mixture of 2,66 g Ethoquad C-12, 3 g Tergitol 15-S-30, 6 g Tergitol TMN-6, 256 g water and 100 g monomer was mixed in a glass beaker and heated to 40° C. The mixture was sonicated using a Branson sonicator at maximum setting for 4 minutes to obtain a monomer dispersion.
[0081] The monomer dispersion was transferred to a three-necked round-bottom flask equipped with a cooler, a stirrer and a temperature controller. 0.25 g of V-50 initiator was added to the resulting monomer dispersion, and the flask was then purged with nitrogen and then reacted at 70° C. for 16 hours. This gave a high-quality water-based polymer dispersion containing 30% solids.
[0082] Example CLA 30 2404 GMA HOEMA HOEA ODMA ODA C1 100 1 97.5 2.5 2 95 5 3 92.5 7.5 4 90 10 5 85 15 6 80 20 7 75 25 8 70 30 9 60 40 10 50 50 11 40 60 C2 100 12 95 5 13 90 10 14 80 20 15 70 30 16 60 40 17 90 5 5 18 75 25 19 50 50 20 75 25 21 50 50 22 95 5 23 95 5 24 90 10 25 90 10(1*) 26 95 5(2*) 27 95 5(3*) 28 95 5(4*)
[0083] 1*——Contains CHPMA instead of HOEMA
[0084] 2*——Contains Karenz AOI-BP instead of HOEMA
[0085] 3*——Contains Karenz MOI-BP instead of HOEMA 4*——Contains Karenz MOI-BM instead of HOEMA
[0086] Table 2 - Test results
[0087]
Claims
1. An article comprising a substrate and a copolymer disposed on at least a portion of the substrate, wherein the copolymer comprises: a) 50 to 95 wt% of first polymerized units, the first polymerized units comprising at least one of: a1) or a2) in: Each R 1 are independently H or methyl; Each R 2 are independently methyl or ethyl; Each R 3 are independently methylene, ethylene or propylene; Each R 4 are independently methyl, ethyl, propyl or butyl; Each n is independently an integer from 2 to 10; and b) 5 to 50 wt% of polymerized units represented by the formula: in: Each R 6 are independently methylene, ethylene or propylene; and X is an epoxy group; and c) up to 20% by weight of other comonomers.
2. The article of claim 1, wherein the copolymer is non-fluorinated.
3. The product according to claim 1 to 2, wherein R 1 It is methyl.
4. The product according to claims 1 to 3, wherein R 2 It is methyl.
5. The product according to claims 1 to 4, wherein R 3 It is propylene.
6. The product according to claims 1 to 5, wherein R 4 It is methyl.
7. The article according to claims 1 to 6, further comprising a third polymerized unit, wherein the third polymerized unit is represented by the following formula: in: Each R 6 are independently methylene, ethylene or propylene; and X is hydroxyl.
8. The article of claim 1 to 7, wherein the copolymer has one or more of the following properties: i) the initial water repellency of the fabric is at least 70, 80, 90 or 100 according to AATCC TM 22-2017e; ii) the fabric has a water repellency of at least 50, 60, 70, 80, 90 or 100 after washing and drying; and iii) The initial oil repellency of mineral oil or olive oil is A or B according to AATCC TM1 18-2013e2.
9. The article of claim 1 to 8, wherein the substrate comprises porous surfaces including paper, woven and nonwoven fabrics, natural and synthetic leather or suede; and hard surfaces including concrete and natural and synthetic wood and stone.
10. A copolymer, comprising: a) 50 to 95 wt% of first polymerized units, the first polymerized units comprising at least one of: a1) or a2) in: Each R 1 are independently H or methyl; Each R 2 are independently methyl or ethyl; Each R 3 are independently methylene, ethylene or propylene; Each R 4 are independently methyl, ethyl, propyl or butyl; Each n is independently an integer from 2 to 10; and b) 5 to 50 wt% of a second polymerized unit, the second polymerized unit being represented by the formula: in: Each R 6 are independently methylene, ethylene or propylene; and X is an epoxy group; and c) up to 25% by weight of other comonomers.
11. A copolymer, comprising: a) 50 to 95 wt% of first polymerized units, the first polymerized units comprising at least one of: a1) or a2) in: Each R 1 are independently H or methyl; Each R 2 are independently methyl or ethyl; Each R 3 are independently methylene, ethylene or propylene; Each R 4 are independently methyl, ethyl, propyl or butyl; Each n is independently an integer from 2 to 65; and b) 5 to 50 wt% of a second polymerized unit, the second polymerized unit being represented by the formula: in: Each R 6 are independently methylene, ethylene or propylene; and X is independently a functional group selected from epoxy, hydroxyl or isocyanate; and c) 0 to 10% by weight of other comonomers.
12. The copolymer of claim 11, further characterized by claims 2 to 7.
13. An article comprising a substrate and the copolymer according to claims 11 to 12 disposed on at least a portion of the substrate.
14. The article of claim 13, further characterized by claims 8 to 9.
15. A method for preparing an article, the method comprising: applying a water-based dispersion comprising a copolymer according to claims 9 to 12 to a substrate; as well as Water is removed from the dispersion.